International and regional capital mobility in Latin American countries - Yersh, Valeryia (Technological and Economic Development of Economy, 2022)
This study examines the role of global, regional and domestic saving for domestic investment financing in the panel of Latin American and Caribbean countries along with its three regional integration blocks, namely SICA, Andean Community and MERCOSUR. Panel regression and rolling-window estimation results reveal that global saving is the main source of domestic investment financing in the region of Latin America and the Caribbean, SICA, Andean Community and MERCOSUR. The role of domestic and regional savings is rather limited, implying that there are weak regional and domestic channels that can funnel domestic and regional savings into investment in the analysed samples. The importance of regional agreement saving is insignificant and decreases over the analysed period except for the Andean Community. The results indicate low financial integration of the member-countries within the three regional trade agreements.First published online 12 January 2022